Gastrointestinal Protozoan Infections and Associated Factors among Children under 5 Years with Diarrhea in Kisii County, Kenya (Global Journal of Medical Research, 2020)
Globally every year, it is projected that approximately two million infections related to diarrhea occur among children who have not reached their fifth birth anniversary. In Kenya, gastro intestinal protozoan infection is a major problem primarily due to fecal contamination of food and water causing high morbidity. The aim of this study was to establish the predisposing factors associated with gastro intestinal protozoan infections in children under five years with diarrhea in Kisii county, Kenya.
Keywords: gastro intestinal protozoans; diarrhea; children under five years